Deflection and cracking behavior of RC beams externally reinforced with carbon fiber laminates - Norsuzailina, Sutan; Habibur Rahman, Sobuz; Ehsan, Ahmed (SAGE Publisher, 2011)
This article presents the results and discussions of experimental and analytical work on CFRP-strengthened RC beams investigating the cracking and deflection performance. The aim of this study is to evaluate the time-dependent behavior by different degrees of strengthening scheme and two types of sustained loads. Eight RC beams were cast and tested under sustained loads for cracked and uncracked section. An analytical method based on EMM is developed to predict the time-dependent behavior of CFRP externally bonded RC beams. A simplified tension stiffening model for calculating the time-dependent deflection is modified for CFRP-reinforced concrete beams.